An examination of the relationship between companies' corporate social responsibility (CSR) activities and consumers' purchase behavior - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2014)
This research study investigates the relationship between companies' corporate social responsibility (CSR) activities as a marketing strategy and consumers' purchase behavior orientation towards companies' products and services. The main aim of the study is to explore the role of companies' CSR activities in the purchase orientation of the consumers for the products of companies. Based on the previous literature sources and empirical research findings about the relevant subject, it is assumed that the consumers' purchase behavior orientation would be one of the consequences of companies' CSR activities that are undertaken as a marketing strategy. In order to get meaningful data about the subject, a study in Turkish context was conducted on one main holding group that has well-known CSR projects in Turkey. After a review of previous empirical and theoretical studies, general explanations about the subject were made which obtained data for understanding the main proposition of the current study. © 2014 Springer-Verlag Berlin Heidelberg. All rights are reserved.